Contextual Learning Design Based on Islamic Values: Integrating Simplicity, Anti-Waste, and Social Concern in Responding to Global Challenges - Faizal Hakim; Hani Fadilah; Halimah Halimah; Rina Farah; Zain Nizam (Journal of Paddisengeng Technology, 2026)
Background. Contemporary global challenges such as excessive consumption, resource waste, environmental degradation, and social inequality require educational approaches that connect ethical values with responsible action. Islamic values of simplicity, anti-waste, and social concern offer a relevant moral foundation, yet their integration into systematic contextual learning remains limited. Purpose. This study aimed to develop and examine a contextual learning design based on Islamic values that integrates simplicity, anti-waste behavior, and social concern in responding to contemporary global and local challenges. Method. The study employed Educational Design Research involving 61 students of an Islamic Religious Education program at a private higher education institution in South Sumatra, Indonesia. Data were collected through expert validation, student response questionnaires, observation sheets, and value-based learning assessments, and analyzed using descriptive and inferential statistics.Novelty. The study proposes a Context Value Reflection Action (CVRA) instructional pathway that transforms Islamic values from normative concepts into contextual reasoning, critical reflection, and responsible action. Results. The developed design achieved high validity (Aiken’s V = 0.91), high practicality (87.0%), and strong implementation (91.4%). Students’ mean scores increased from 62.18 to 81.46, with a significant difference, t(60) = 14.82, p < .001, and a large effect size (d = 1.90). Anti-waste awareness showed the greatest improvement. Conclusion. The CVRA-based contextual learning design provides a promising framework for integrating Islamic values with sustainability and social responsibility, although long-term value internalization requires continuous practice and institutional reinforcement.